Federated Service Management a federated approach to managing highly distributed web services. - Candadai, Arun (SOA webservices journal.)
Service oriented architecture (SOA) has emerged as a key strategy for IT and line of business executives to jointly enhance business performance and agility in today's intense corporate climate. Using the SOA methodology, business applications are built as an assembly of loosely coupled pieces of business functionality, commonly referred to as services. These services are published, consumed and combined with other applications over a shared services network, which is often highly distributed within and across enterprise boundaries.